MITO: A new operational model for the forecasting of the Mediterranean sea circulation - Napolitano, E.; Iacono, R.; Palma, M.; Sannino, G.; Carillo, A.; Lombardi, E.; Pisacane, G.; Struglia, M. V. (Frontiers in Energy Research, 2022)
Availability of detailed short-term forecasts of the ocean main characteristics (circulation and waves) is essential for a correct management of the human activities insisting on coastal areas. These activities include the extraction of renewable energy, which has developed in recent years, and will play an important role in the context of future blue growth. The present work describes the implementation of a new ocean operational system, named MITO, that provides daily 5 days forecasts of the Mediterranean Sea circulation. Distinctive features of this system are the inclusion of the main effects of the tidal forcing, both local and propagating from the Atlantic, and the high spatial detail. The horizontal resolution is of 1/48° (about 2 km) in most of the computational domain, and is smoothly increased (down to few hundred meters) in key passages, such as the Gibraltar Strait and the Turkish Straits, to correctly resolve the complex local dynamics. Initial and boundary conditions for MITO are taken from the reference European operation model of Copernicus, which covers the Mediterranean Sea with a uniform resolution of 1/24°. A thorough validation of the new system is performed, analyzing the forecasts of the year 2020, whose results are compared with in situ and remote observational data (sea surface temperature, altimeter data, temperature and salinity profiles by floats, tide-gauge measurements, available through the Copernicus portal) using the same large-scale metrics applied in the validation of the Copernicus operational model. MITO results are generally found in very good agreement with the observations, despite the fact that the model does not make explicit use of data assimilation. We also give examples of the capability of the model to correctly describe complex local mesoscale dynamics, and point out aspects that need to be improved, which will be addressed in a future upgrade of the operational implementation.